Preparing Future Teachers for Innovative Pedagogical Activities - To’lqinjonovna, Sadullayeva Zarnigor (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, future school, university, academy teachers to innovative professional activity an opinion about the unique pedagogical and psychological features of the training process held. It is also pedagogical in preparing them for innovative professional activities description of practice, best practices and issues of cooperation with parents mechanisms of training of future innovative pedagogues are envisaged.